2005
DOI: 10.1080/00908310490441980
|View full text |Cite
|
Sign up to set email alerts
|

Source Rock Evaluation of the Lacustrine Oil Shale Bearing Deposits: Göynük/Bolu,Turkey

Abstract: Paleocene Kabalar Formation (Göynük, Bolu/Turkey) has been studied by a combination of organic geochemical methods (LECO/Rock-Eval, gas chromatography), light microscopy and bulk combination method (elemental analysis) in order to assess the hydrocarbon source potential of the abundant and extensive lacustrine shale intervals present in the formation.The organic matter in the shales is an algal material (type I kerogen) having a rich oil potential. The shales have an organic carbon content of up to 10% and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…explicitly indicates a brahic to epineritic environment. Sarı and Aliyev (2005) reached the same conclusion by using total organic carbon (TOC) and total sulfur (TS) contents of the Hatıl dag oil shales. They showed that the Kabalar samples (mostly equivalent of our Hatıl section in Fig.…”
Section: Lacustrine Deposits Of the Mudurnu-göynük Basinmentioning
confidence: 55%
See 1 more Smart Citation
“…explicitly indicates a brahic to epineritic environment. Sarı and Aliyev (2005) reached the same conclusion by using total organic carbon (TOC) and total sulfur (TS) contents of the Hatıl dag oil shales. They showed that the Kabalar samples (mostly equivalent of our Hatıl section in Fig.…”
Section: Lacustrine Deposits Of the Mudurnu-göynük Basinmentioning
confidence: 55%
“…Average calorific value and the mean oil yield for this resource are 3.24 MJ/kg and 5.3 wt.% respectively. Sarı and Aliyev (2005) suggested that shales of the area comprise algal material (type I kerogene) having a rich oil potential. Their pyrolysis works further demonstrated that oil-shale bearing lacustrine unit has probably entered thermal zone of oil generation and may produce oil.…”
Section: Regional Depositional Patterns In the Eocene Of Anatolian Bamentioning
confidence: 99%
“…Even short-term oxygenation of anoxic sediments 484 may result in rapid dissolution of authigenic uranium (Cochran 485 et al, 1986;Anderson et al, 1989). Since HOS was deposited in 486 lacustrine environment with continuously varying water level 487 (Saner, 1978;Sarı and Aliyev, 2005) Uncited reference 563 Sener and Sengüler (1998). …”
mentioning
confidence: 99%
“…Therefore; bituminous rocks around the study area has also been the subject of many investigators from the point of hydrocarbon and element enrichments view (Şeker and Kesgin, 1991;Sari and Sonel, 1995;Şener and Şengüler, 1998;Büyükutku et al, 2005;Sari and Aliyev, 2005;Aliyev et al, 2006;Sari et al, 2007;Kara and Korkmaz, 2008;Sari and Geze, 2008;Şengüler, 2012).…”
Section: Introductionmentioning
confidence: 99%